A Comparative Corrosion Study of Al/Al2O3-SiC Hybrid Composite Fabricated by Accumulative Roll Bonding (ARB) - Mohsen Reihanian (Journal of Ultrafine Grained and Nanostructured Materials, 2016)
In this study, the Al/Al2O3-SiC hybrid composite was produced by accumulative roll bonding (ARB). In the first and the second cycles, the particles were uniformly poured between the Al strips during each ARB cycle. In the subsequent cycles, ARB was repeated up to six cycles without adding the particles between the layers. After the total eight cycles, the particles were distributed uniformly without agglomeration in the Al matrix. The corrosion behavior of the hybrid composite was investigated and compared with that of the annealed and ARB processed Al. The corrosion tests were conducted by the potentiodynamic and electrochemical impedance spectroscopy tests in 3.5 wt-% NaCl solution. The anodic potential of the pure Al processed by ARB was more positive than that of the annealed Al while its corrosion current density was higher. The corrosion potential of the hybrid composite was somewhere between the annealed Al and ARB processed Al. The hybrid composite exhibited the lowest current density and the highest charge transfer resistance. The increased corrosion resistance of the hybrid composite was attributed to the inert character of the Al2O3 and SiC particles because these particles could decrease the active sites of the material surface and impeding the corrosive attacks.